«Prima natura, secunda doctrina, tertia felicitas». Aeneas as a hero in the making (and an educational model) in Fulgentius’ “Virgiliana continentia” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
At the turn of the fifth and sixth centuries, in North Africa, Fabius Fulgentius Planciades wrote a short text dedicated to the interpretation of the Aeneid. Within the structure of a dialogue between the author and Virgil, the poem is read as an “integral” allegory, which presents sub figuralitate historiae the moral maturation of Man’s soul through the physiological progression of the ages of life. In this journey, Aeneas is the hero in a Bildungsroman, but he also becomes an educational model in a concrete sense and within a broader and more consistent pedagogical scheme.
Keywords: Fulgentius; Aeneas; Virgiliana continentia; Late Latin Literature; Allegory; Etimology